Study on the effects of fissure geometric characteristics on the mechanical behavior and failure mechanism of granite under uniaxial compression test - Sang, Zhaolong; Ma, Donghui; Meng, Yaoyao; Yin, Qian; Liu, Xiaowei; Sun, Zhimin; Wang, Wei (Scientific reports, 2025)
Taking the granite specimen with multiple fissures as the main research object, the mechanical response and failure mechanism of the granite specimen under uniaxial compression tests were analyzed by constructing a numerical analysis model based on cohesive element and Voronoi polygons techniques. Furthermore, the effects of geometric characteristics (spacing, length, width) on the peak mechanical response, damage energy, number and proportion of micro-cracks, failure mode and so on are further studied. The results show that the numerical analysis model can accurately reproduce the complex intergranular occlusion and multi fissures network structure of granite specimens, and reveal the dominant role of fissure angle on the failure mode, and the significant influence of fissure geometric characteristics on the number and proportion of micro-cracks, peak mechanical response and damage energy. The crack path and failure mode are significantly affected by the change of fissure angle and spacing, while the increase of fissure length and width leads to more rapid failure and lower peak mechanical response. The damage energy increases gradually with the increase of fissure spacing, but decreases with the increase of fissure length and width. This study not only deepens the understanding of the mechanical behavior of granite samples under complex geological environments, but also provides theoretical support for accurate assessment and effective reinforcement of rock mass stability in engineering practice.